An instrument, design and implemention of a temperature control´s system for a drying paper chamber´s prototype, at scale (2017)
This is brief description of the design and implementation of a temperature digital control system for a drying chamber's prototype at scale of the company "Industrias Explorer". The prototype implementation was carried out using some suitable sensors for measuring the temperature and the relative humidity. As the actuator system was used some heating resistors made from an alloy Fe-Cr-Al. In addition, an interactive interface was constructed, where the signals involved in the process developed by the company are monitored and recorded. For the controller design and the interface was used a DSP card, manufactured by the instruNet and programmed at the Lab View.